6x+4(-4x-14)=-176

Simple and best practice solution for 6x+4(-4x-14)=-176 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+4(-4x-14)=-176 equation:


Simplifying
6x + 4(-4x + -14) = -176

Reorder the terms:
6x + 4(-14 + -4x) = -176
6x + (-14 * 4 + -4x * 4) = -176
6x + (-56 + -16x) = -176

Reorder the terms:
-56 + 6x + -16x = -176

Combine like terms: 6x + -16x = -10x
-56 + -10x = -176

Solving
-56 + -10x = -176

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '56' to each side of the equation.
-56 + 56 + -10x = -176 + 56

Combine like terms: -56 + 56 = 0
0 + -10x = -176 + 56
-10x = -176 + 56

Combine like terms: -176 + 56 = -120
-10x = -120

Divide each side by '-10'.
x = 12

Simplifying
x = 12

See similar equations:

| 5m^2-50m=0 | | 4x+3(-3x+13)=89 | | 7+(-5)=12 | | 0=0.3*4180*(t-20)+0.1*385*(t-400) | | x-3x+5=3x-0.5 | | 2x+3*2=5x+4 | | x-3x+5=3x-1 | | 5m(2m^2-n^3)= | | (5n-18)+(2n+12)=180 | | 3+5x=x+15 | | (4x-1)(x-9)=0 | | -3(m+4)=4 | | y=(7x+9)(x-1) | | 105=-3x+5(-3x+3) | | 7m-3m+4=16 | | 5lnx=30 | | 18y=12-12x | | =2500-2x | | 7x-6=3(x^6) | | (12x+10)-(-4x-6x+10)= | | 6[-6x+6+4x(x+1)]=6x+2 | | 0.5x+0.25=x | | 3x+3(5x-10)=138 | | (2mn+8m^2n-5n+6m)= | | 0=(t-20)+(t-400) | | 8.57x+17.14=34.28 | | t-20=t-400 | | (2mn+8m^2n-5n+6m)(10mn^2)= | | 3cos(x)=8-4sec(x) | | Y=2500-2x | | 10x+4x+4+9=4x+3+9x | | x^2+4x=47 |

Equations solver categories